EFFECT OF LOCALLY ISOLATED SCENEDESMUS SP. TN1 ON BIOMASS PRODUCTION AND NUTRIENT REMOVAL FROM COOKING COCOON WASTEWATER: EFFECTS OF INITIAL ALGAL CELL DENSITY AND TEMPERATURE - Le, Thi Anh Tu (Trường Đại học Đà Lạt, 2024)
Scenedesmus sp. TN1, a local freshwater microalga, was cultivated in cooking cocoon wastewater. The effects of initial algal cell density and temperature on microalgae growth and the removal of total nitrogen (T-N), total phosphorus (T-P), and chemical oxygen demand (COD) were studied. The initial algal cell densities were 5, 10, 15, and 20 mg/l. The experimental temperatures varied from 20 °C to 30 °C. The growth rate increased with the increase in initial algal cell density up to 15 mg/l and was statistically stable thereafter. A similar trend of total nitrogen, total phosphorus, and COD removal efficiency was observed. The optimum temperature for microalgae growth and nutrient removal was 30 °C. After 9 days of cultivation, Scenedesmus sp. TN1 exhibited nutrient removal efficiencies of 88.28%, 82.91%, 92.01%, and 89.16% for T-N, T-P, biological oxygen demand (BOD5), and COD, respectively. The maximum biomass production and nutrient removal efficiencies of Scenedesmus sp. TN1 were observed at cultivation conditions of 15 mg/l initial algal cell density at 30 °C. This study compiled information on the cultivation conditions for cooking cocoon wastewater treatment practices.